Perlindungan Korban dalam Penanganan Post Traumatic Stress Disorder pada Tindak Kejahatan Bullying pada Remaja di Indonesia - Ananda Ima Saputri; Ridwan Arifin (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2022)
This writing aims to determine the impact of bullying crime from the point of view of victims of bullying who get stressed post-traumatic stress disorder so that victims need to get protection from the incident. In the 1945 Constitution article 28B (paragraph 2) it has been explained that: